Students' Mathematical Literacy Ability in Solving Problems on Pattern Material Using the Bengkulu Local Contexts - Agus Susanta; Hari Sumardi; Edi Susanto (Didaktik Matematika, 2022)
Mathematical literacy is an important ability for students in Indonesia to face the implementation of minimum competency assessment and learning in the 21st century.This study aims to describe students' mathematical literacy skills in solving problems on pattern material in the Bengkulu local context. This study used a descriptive qualitative design. The research subjects were 30 students grade VIII from five schools in Bengkulu City. Subject selection through purposive sampling technique based on the level of intelligence with the number of each school is six students. Data were collected through interviews and mathematical literacy test using description questions that have been validated and tested. The data analysis consists of data reduction, data presentation, and concluding. The findings of this study are that students with low to moderate knowledge tend to have literacy skills at level 2. In contrast, students in the high knowledge group have literacy skills at level 3. Many students have used mathematical arguments to solve literacy problems but did not use concepts correctly.Students have not used the model structurally at the modeling stage, which resulted in errors in problem-solving and representation. Based on this, teachers need to emphasize the concept of material and mathematical modeling in learning.